Frequency dependence of dielectric parameters of structure with Bi3.25La0.75Ti3O12 thin film prepared by sol-gel method - Tataroglu, A.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Natl Inst Optoelectronics, 2017)
In this study, the frequency dependence of dielectric parameters of Bi3.25La0.75Ti3O12 (BLT) thin film prepared on Al-coated p-type silicon substrate by sol-gel method were investigated using admittance (Y=G+i omega C) measurements. These measurements were carried out in the frequency range of 10 kHz-1 MHz. The frequency dependence of the capacitance (C) and conductance (G/omega) indicates the existence of interface states. Dielectric constant (epsilon'), loss (epsilon '') and loss tangent (tan delta), ac conductivity (sigma(ac)) and complex electric modulus (M) values were calculated from impedance measurements. It has been found that the epsilon' and epsilon '' decrease while the sigma(ac) increases with the increasing frequency. Experimental results show that the values of dielectric parameters are a strong function of frequency.
Keywords: Bi325La0.75Ti3O12 (BLT) thin film; Dielectric parameters; Frequency dependence